An improved solar PV system for Malaysian rural electrification - Part II: Implementation and economic analysis of solar PV system with tracker and reflectors - Malek N.B.Abd.; Hasini H.B.; Rahman A.B.Abd.; Jaafar Mohd.N.B.Mohd. (2023)
This paper is the second of a set describing the implementation and economic analysis of an improved solar photovoltaic (PV) system for Malaysian rural electrification. The work was carried out based on a case study in a rural community to replace their diesel-powered generators with the new renewable energy (RE) solutions, with buffer capacity for additional requirements. Based in the extensive tests done on the system, it is proven that the new improved design of solar power system can be implemented as it meets the technical requirements of the project. Considering not only the technical requirement, it is also important to design the implementation and maintenance schedule of the system since the local communities have no or little exposure to this system. With adequate trainings and briefings, the maintenance schedules can help them to get involved in the operation and maintenance of the system. Other than that, the economic value of a PV system is calculated so that it can be compared with other methods of power generation. The details of the implementation of solar power system and its impact to the community are discussed in this paper. 2010 IEEE.